Pelanggaran Administrasi Pemilu Penyelenggaraan Pemungutan Suara Ulang Pada Pemilu Serentak 2019 Di Kabupaten Bangka Tengah - Ricky Febriansyah; Hertanto Hertanto; Arizka Warganegara (Jurnal Pemerintahan dan Politik, 2021)
The reason for the recommendation of Re-Voting (PSU) by the Election Supervisory Board (Bawaslu) of Central Bangka Regency is that voters who do not have the right to get votes are given the opportunity to exercise their rights. This is an indication of the election administration violation and negligence of the Voting Organizing Group (KPPS) in carrying out its duties and obligations. PSU took place at TPS 10 Beluluk Village and TPS 04 Air Mesu Village, Pangkalan Baru District. This study aims to determine the electoral administration violations and negligence of the KPPS as the cause of the Bawaslu recommendation. By using descriptive qualitative research methods through interviews with election organizers, literature study and documentation. The results showed administrative violations because the KPPS had difficulties in distinguishing the types of voters. The negligence of KPPS is a form of accidental duty caused by the lack of understanding of KPPS, heavy workload, pressure from voters who are enthusiastic, lack of coordination between TPS supervisors and KPPS and KPPS feels experienced.Keywords: Administrative Violations, Negligence, Voting Again (PSU)